(3GdeMGSHI GdEOGQjIs - (3YUGe agO(B, (3GdYQHjOs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2002)
(3hXGFa GdeMGSHI GdEOGQjI(B- (3GdeMGSHI GdEOGQjI hJHhjH GdJcGdja(B- (3GdeMGSHI GdEOGQjI hGdeMGSHI Yf GdehGO GdChdjI hGdCLhQ hGdeUGQja ZjQ GdeHGTQI(B- (3GdeMGSHI GdEOGQjI hJcdaI ChGeQ GdJTZjd hJcdaI GdYbhO(B- (3GdeMGSHI GdEOGQjI h JcdaI GdYedjGJ (B- (3GdQbGHI hGdJNWjW (B- (3EYOGO GdehGRfI(B- (3GdeMGSHI GdEOGQjI hGdJcGdja GdeYjGQjI(B-(3Jbhje GdGOGA(B- (3bjGS GdQHMjI hEJNGP GdbQGQJ aj GdCLd GdbUjQ(B- (3GdJWhQGJ GdMOjKI aj bjGS GdQHMjI h GdCOGA(B- (3CaGb GdeMGSHI GdEOGQjIs
Keywords: (3EOGQI GdCYeGds; (3GdeMGSHIs; (3GdeMGSHI GdEOGQjIs